PROBLEMATIKA PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN ORANG SEBAGAI KEJAHATAN TERORGANISIR TRANSNASIONAL OLEH DIREKTORAT RESERSE KRIMINAL UMUM KEPOLISIAN DAERAH RIAU - Rullyansyah Qotni Putra; Erdiansyah Erdiansyah; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The regulation of human trafficking has been regulated in the Law Number 21 of 2007concerning the Eradication of the Crime of Human Trafficking. However, the efforts of theIndonesian government in implementing various policies to combat and prevent cases ofhuman trafficking do not reflect as we expected. This problem is derived that’s faced by theinvestigator when carrying out investigative activities in the field. The main issues in this studyare: How are the implementations of law enforcement against the perpetrators of the crime ofhuman trafficking as a Transnational Organized crime by the Directorate of General CriminalInvestigation of the Riau Regional Police; What are the obstacles and law enforcement effortsagainst the perpetrators of the crime of human trafficking as a Transnational Organized Crimeby the Directorate of General Criminal Investigation of the Riau Regional Police.This type of research is sociological legal research conducted at Sub Directorate IV ofthe Directorate of General Criminal Investigation of the Riau Regional Police. The datasources used are primary data and secondary data. Data collection techniques were carriedout by interviews and literature review. The data were analyzed qualitatively which produceddescriptive and meaningful data using deductive thinking methods.The results of this research are law enforcement against the perpetrators of humantrafficking has been divided into preventive and repressive manner. Example preventive lawenforcement efforts are in the form of counseling, outreach, seminars or outreach to the public.Meanwhile repressive law enforcement begins with investigative activities. Obstacles in thisimplementation are: the local communities being secluded and does not want to cooperate withthe investigators; Strategic location of Riau Province; Limited investigative budget;Inadequate facilities and infrastructure; Lack of human resources in Sub Directorate IV of theRiau Regional Police's Criminal Investigation Unit. Efforts that can be made to overcome theseobstacles are: Making a humane approach towards local community; Conduct an outreachand socialization efforts to the community; Establishing cooperation by making memorandumof understanding with related agencies; Submission of budget proposal; Proposing assistancein terms of additional facilities and infrastructure to support investigative and investigativeactivities; Proposal to involve investigators to attend training, courses, further educationKeywords: Trafficking in Persons – Investigations – Organized Crime